Digital library technology in J-ISIS : concept, implementation and comparison with GSDL - de Smet, Egbert (2014)
Presents a report on some necessary DL technological requirements, such as the capability to deal with any metadata structure and alphabets and full text indexing of documents of any length, and how J-ISIS can deal with these, as well as on the production of DL interface for digital library applications based on Tika technology.